OPTION FOR THE ADVISABILITY OF APPROPRIATE AIRCRAFT USE DURING THE PROLONGED SEARCH AND RESCUE OPERATIONS - A. V. Sobolev (Naučnyj Vestnik MGTU GA, 2018)
Carrying out search and rescue operations (SAR) in a unified system of aerospace search and rescue (ASR) is not only related to the use of on-duty search and rescue (OSR) aircraft, but also with the need to attract additional forces and assets, including non-regular aircraft. At the same time, the cost of carrying out the SAR is significantly increased during prolonged searches. The article presents a problem solution for reducing the cost of conducting prolonged SAR by the method of expedient use of aircraft in compliance with the necessary system requirements. Studies of last years in this field have hardly considered the specifics of conducting searches in this context. For this purpose, an analysis of the current conditions for the implementation of the SAR is carried out and key options for the use of aircraft are considered. It has been revealed that the amount of the search work is much greater than the amount of evacuation work. Therefore, the main charge of financial resources for the use of aviation in the SAR falls to the search phase. A rationale for the use of light aircraft in the search phase is suggested, for example, to replace some regular (on duty) Мi-8 helicopters instead of the Мi-2, the search capabilities of which are almost identical. The peculiarity of the application is the possibility of carrying out flights by the guidance method. As an example, an SAR with a prolonged phase was considered, in which it was theoretically possible to reduce costs by 8.3%. The proposed method provides a basis for a rethinking of the aircraft modern equipment for the SAR of the regional search and rescue bases in favor of small and less heavy lifting when carrying out prolonged SAR. At the same time, the economy of financial resources is ensured, taking into account the observance of the necessary requirements of the ASR system regarding its effective functioning as a whole.